Surface Modification of ZrO[2] -3Y[2]O[3] Ceramics with High-Intensity Pulsed N{2+} Ion Beams; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Kostenko V. Valeriya; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Xiaopeng Zhu; Pushkarev A. I. Aleksandr Ivanovich; Egorova Yu. I. Yulia Ivanovna; Matrenin S. V. Sergey Veniaminovich; Zhang C. C.; Lei M. Mingkai; Surzhikov A. P. Anatoly Petrovich (Ion Beam Processing of Materials. Poster Session, 2019)
Заглавие с экрана